Penguatan Kelembagaan Sekolah Inklusi di Kabupaten Banyumas: Bebas Tiga Dosa Besar Pendidikan - Chamadi, Muhamad Riza; Tyas Retno Wulan; Tri Wuryaningsih; Tri Rini Widyastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIN Prof. K.H. Saifuddin Zuhri, 2025)
Education is a basic right of every citizen guaranteed by various national regulations. However, in prac-tice, inclu-sive schools in Indonesia still face various challenges, such as limited teacher competency in handling Children with Special Needs (ABK), minimal facilities and infrastructure, weak institutional systems, and social stigma from the community. This condition has implications for the emergence of the phenomenon of